Model Pembelajaran CIRC (Cooperative Integrated Reading And Composition) sebagai Salah Satu Strategi Pembelajaran Matematika di Sekolah Dasar - I Komang Sesara Ariyana; I Nengah Suastika (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Student's activities in learning mathematics in elementary schools are suggested to be more in reading, writing, communicating, making pictures, tables, and so on, to encourage problem solving, reasoning, and mathematical connection skills. This activity can be stimulated by giving word problems as mathematical problems that must be solved by students. Giving word problems is the right way when mathematics learning is ready to be accepted by students at the application level in everyday life. To support the strategy of giving word problems to stimulate student learning activity, the CIRC learning model can be applied. CIRC stands for Cooperative Integrated Reading and Composition, is a cooperative learning model that encourages active students to read and write in small groups. Word problems become a support system in learning mathematics by applying the CIRC learning model. By applying the CIRC learning model, students do more reading, writing, communicating, and even arguing and debating in math class. So that students' understanding of mathematics material will be stronger, and students' learning activities and mathematics outcomes will be better.